Droplet migration on hydrophobic–hydrophilic hybrid surfaces: a lattice Boltzmann study. Issue 24 (6th March 2017) - Li, Q.; Yu, Y.; Zhou, P.; Yan, H. J.
Abstract : Droplet migration on textured hydrophobic–hydrophilic surfaces. Abstract : In this paper, the fundamental features and mechanism of droplet migration on hydrophobic–hydrophilic hybrid surfaces are investigated using the lattice Boltzmann method. The hybrid surfaces are textured with pillars, which consist of hydrophobic side walls and hydrophilic tops. First, we study the cases with wettability differences between the sides and the tops of the pillars. It is found that, with an insufficient wetting contrast, the upper contact lines are pinned at the edges of the top surface. With an increase of the contact length between the droplet and the side wall of the pillar, a larger wettability difference is required to induce droplet migration. Meanwhile, it is observed that the migration process is gradually speeded up when the droplet covers more hydrophilic regions of the pillar. Moreover, the influence of the bottom substrate's wettability is investigated. Two types of hybrid surfaces are considered, one of which adopts a wettability difference between the bottom substrate and the sides of pillars. The results show that the droplet migration can be promoted by applying a wetting contrast between the bottom substrate and the sides of the pillars, because the contact length between the droplet and the surface can be reduced with an increase in the hydrophobicity of the bottom substrate.